Simulation and Parameteric Studies on Reactive Dividing Wall Distillation Column - Kaur, Jasdeep (My University, 2019)
Sustainable development has been advocated as an overarching goal by the government, non-government organizations and scientists. Saving energy and fuels in process industries is being considered as a serious objective among developing and non-developing economies of the world due to depleting fossil fuels reserves. So, there comes an urgent need to develop technologies which would help to achieve this objective in industries. Most chemical and petrochemicals units involve production and purification of chemical products in the course of their making. For separation and purification of the liquid products in the CPI, distillation remains a promising choice despite of significant developments in other fields of separation media. About 95% of liquid separations in CPI are carried out using distillation as a separation technology. Due to energy intensive nature of these units, energy-efficient distillation design and operation are the major concerns in CPIs. For significant reductions in capital and energy savings, as well as environmental benefits, researchers have been working on process intensification (PI) of distillation processes. A great breakthrough in this field was made with the invention of Dividing wall distillation column (DWC). DWC and reactive dividing wall column (RDWC) are an example of high level process intensification, which have substantially reduced energy requirements. RDWC is a case of high degree of process intensification, as it involves reaction and separation of high purity of components of the reaction mixture in a single shell. It has two sections, reaction takes place on one side and products are separated on other side of the wall. A number of studies report the use of RDWC for the production of different fuels, fuel additives and solvents (discussed in next section). It has been reported that RDWC produces products of high quality for a number of liquid and gas reaction systems. The present work focuses to study production of upcoming fuel additive ethyl tertiary butyl ether (ETBE) and a very popular industrial solvent ethyl acetate (EtAc) via RDWC. The motivation behind using RDWC for the synthesis of these systems is the energy saving aspect of RDWC. ETBE is an upcoming oxygenate which could be added to gasoline to improve its characteristics. There are no studies in the literature which report the synthesis of ETBE via RDWC. A mathematical model of RDWC for the two reaction systems has been developed for the synthesis of ETBE and ethyl acetate. MESHRD equations have been written, taking into account the effect of pressure drop across the dividing wall in the column. For the mathematical model equations of RDWC, degree of freedom analysis was carried out, and its value came out to be four. The present work focused on simulation studies of RDWC for the ETBE and ethyl acetate synthesis Aspen plus V.8.1. Four different process alternatives which could possibly be applied for the synthesis of ETBE were studied, namely, reactor plus distillation sequence, reactive distillation unit, reactor accompanied by reactive distillation and RDWC. A comparative study of the alternatives was done in terms of energy requirements, carbon dioxide emissions and costs. The comparison results showed that RDWC is best alternative out of the four. Significant savings were observed when process intensification was done for the process of production of ETBE. The RD unit was found to have energy requirements of 373.38 kWh/t-ETBE. The energy requirements for RD was drastically reduced by 50.5%. The energy requirements of the reactor plus RD unit were 414.02 kWh/t-ETBE, this value was less than the conventional sequence. RDWC showed 74% reduction in the energy requirements as compared to the conventional reactor distillation sequence. The energy required by RDWC was found to be 234.94 kWh/t-ETBE, which was 43% less than RD sequence. Process alternatives were also compared in terms costs. The total annualized cost showed a reduction of 53% for RDWC as compared to the conventional sequence. As compared to the given alternatives the total investment costs for RDWC were found to be 41 % less as compared to reactor plus distillation sequence, 4% less as compared to the RD and 68% less as compared to the reactor plus RD sequence. The CO2 emissions were 74% and 43% less in case of RDWC as compared to conventional process for synthesis of ETBE, and RD process, respectively. The product purity of ETBE was found to be highest 99.99% (mol.), in case of RDWC. The value of purity was more than that obtained in case of RD. The product purity for conventional alternative and RD plus DC sequence was lower than RD and RDWC. This comparison was made taking same reflux ratio and similar column specifications for RD, reactor combined with RD and RDWC. Parametric optimization of an RDWC for the synthesis of ETBE was also carried out. This multi-objective mixed-integer optimization was performed for six responses simultaneously using the BBD under RSM. The objectives were, maximizing the purity of the products in distillate, bottom and side stream, and to minimize energy requirements, condenser duty, and CO2 emissions by varying six structural and operational variables of the RDWC while maintaining a zero pressure drop across the dividing wall. This study also helped to identify parameters which affect the responses most significantly, e.g. for ETBE purity these variables were reflux ratio and number of stages. The optimized RDWC had energy requirement of just 839kW with 99.99 mol% purity of ETBE, this value was 30% less as compared to RD. For ethyl acetate system the same comparative analysis was done for two process alternatives. One of the alternative was the conventional sequence involving reactor and RD column and the second was the proposed alternative RDWC. A high purity ethyl acetate was obtained in the present work using RDWC and an overall reduction for the energy requirements of 30% was observed and the same amount of reduction was observed for CO2 emissions for the process which involved RDWC. The benefits of RDWC for the synthesis of two reaction systems suggest RDWC can be used for the synthesis of the two systems and it can save a substantial amount of energy and costs. It can be established as a lucrative option as compared to the conventional systems for the synthesis of several other compounds.
Keywords: Dividing wall Distillation Column; ethyl tertiary butyl ether; ethyl acetate; simulation; energy requirements; optimization